Precision agriculture in the World and its prospect in Bangladesh - Afroj, Mahfuza; Kazal, Mohammad Mizanul Haque; Rahman, Md Mahfuzar (Research in Agriculture Livestock and Fisheries, 2016)
Precision Farming merges the new technologies borne of the information age with a mature agricultural industry. It is an integrated crop management system that attempts to match the kind & amount of inputs with the actual crop needs for small areas within a farm fields. This study is basically based on the secondary data and it is a review paper. As it is a review paper so, there was less opportunity to follow any specific method in preparing this paper. Valuable information has been collected through internet browsing, journals etc. In this paper, we examine that, GPS, GIS, VRT, profitability, yield mapping etc. are most common precision agriculture techniques where, GIS can help in site-specific applications of fertilizers and soil amendments and help effectively detect and map black fly infestations, making it possible to achieve precision in pest control. Remote sensing combined with GIS and GPS can help in site-specific weed management. From the review we observed that, the global adoption of yield monitors has been predominated in North-America and Europe. The precision technologies have been used on a wider variety of crops in Denmark and UK than in the US. In Bangladesh, precision agriculture has great prospect as our country is highly natural calamity sensitive and through it we can easily take measure to prevent our agricultural products from damage caused by natural calamities. Though, precision agriculture is very costly but the benefit from it is more than its cost for most of the developing countries. So, the precision agriculture has great prospect in Bangladesh as well as in the world and it is the utmost time to adopt this technology in our traditional agriculture. Res. Agric., Livest. Fish.3(1): 1-14, April 2016